2010
DOI: 10.1029/2009jd012359
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of a 27 day solar signature in noctilucent cloud occurrence frequency

Abstract: [1] This paper presents evidence of a connection between the 27 day modulation of the solar activity and noctilucent cloud (NLC) occurrence frequency as measured by the Scanning Imaging Absorption Spectrometer for Atmospheric Chartography (SCIAMACHY) and solar backscatter ultraviolet (SBUV) instruments. Observations show anticorrelations significant at the 90% confidence level between noctilucent cloud occurrence rate anomalies and Lyman-a irradiance variation during several seasons in both hemispheres. A supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 53 publications
1
47
0
Order By: Relevance
“…Satellite observations from the Halogen Occultation Experiment [Hervig and Siskind, 2006] and the Solar Backscatter Ultraviolet instruments [Shettle et al, 2009] have shown this anticorrelation of PMCs with Lyman a. Recently, a variation associated with the 27 day solar rotation has also been identified [Robert et al, 2010]. Ground-based results, however, have been less conclusive, with a solar cycle variation identified in only a subset of the available data [Fiedler et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Satellite observations from the Halogen Occultation Experiment [Hervig and Siskind, 2006] and the Solar Backscatter Ultraviolet instruments [Shettle et al, 2009] have shown this anticorrelation of PMCs with Lyman a. Recently, a variation associated with the 27 day solar rotation has also been identified [Robert et al, 2010]. Ground-based results, however, have been less conclusive, with a solar cycle variation identified in only a subset of the available data [Fiedler et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…This should result in less ice-particle formation (von Zahn et al, 2004) and hence should affect PMSE. Variation of solar radiation could also influence atmospheric temperature via production of ozone after photodissociation of O 2 (Robert et al, 2010) and via changing atmospheric dynamics. Kirkwood et al (2010b) have found an empirical relation between PMSE η and ionospheric plasma and ice particle parameters using the 54 MHz radar MARA at Wasa, Antarctica and the SOFIE instrument onboard the AIM satellite.…”
Section: Pmse Volume Reflectivity and Solar Fluxmentioning
confidence: 99%
“…Before averaging the different epochs, anomaly time series are determined by removing an 18 day running mean from each individual time series. The choice of an 18 day running mean is slightly arbitrary, but tests showed that the results obtained using a 15 day or 20 day running mean are very similar, in agreement with similar tests performed for identifying a solar 27 day signature in noctilucent clouds [Robert et al, 2010]. The anomaly time series for OH rotational temperature, OH emission rate, OI emission rate, and atomic oxygen were then smoothed with a 3 day running mean in order to reduce variability.…”
Section: Resultsmentioning
confidence: 56%